Determinants of community dwellers’ participation in self-help community development projects in Ido local government area of Oyo State, Nigeria. (2011)
The study investigated the determinants of community dwellers’ participation in self- help development projects in Ido Local Government Area of Oyo slate in Nigeria. Three wards out of ten that constituted Ido local government were randomly selected. Purposive sampling was used to select one community from each of the three wards due to existence of self-help projects in those communities. Random sampling was used to select 37 respondents from Ido community, 37 were also selected from Onn while 36 respondents were selected from Akufo given the total sample size of 1 10. Data were collected through structured questionnaire and interview schedule. The study revealed that 66.4% of the respondents were male, 65.8% had formal education, majority (73.6%) fell within 19-49 years while 66.9% had income between 1,000 - 20,000 naira. Three projects, school, borehole and market were prominent in the selected communities. Activities undertook by respondents were: awareness creation, identifying community felt need and ensuring sustainability of projects. The study revealed significant relationship between respondents income and participation in self-help projects. Positive correlation existed between the activities undertook by respondents, attitude of respondents and participation in community development projects. Thus, income, activities and attitude of respondents determine the participation of community dwellers in self-help community projects. More income generating activities, positive attitude toward self-help projects and involvement of the entire community in all self- help projects is essential.